Pendidikan Entrepreneurship sebagai Alternatif Menjawab Tantangan Pendidikan Global - Dwi Destiana (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Global competition that demands the development of society in the world, has an impact on the education which becomes the foundation of the nation's scientific. Globally, all nations are vying to improve progress in all areas of technology, economics, and education. Unavailability jobs for the nation's intellectuals, the low economic community, and the competitiveness of the nation, became an internal challenge of Indonesia to be able to fix and strengthen the nation building. Education entrepreneurship comes as an alternative education to answer the challenges of global education. The existence of entrepreneurship education curriculum at every level of education, government and community support, and actualization of entrepreneruship education in universities, become the carrying capacity expected to realize the nation's progress in this global era.